Analisis Pemilihan Vendor Terbaik dalam Pengiriman Produk Minuman dalam Kemasan Menggunakan Metode AHP dan Topsis di PT CS2 Pola Sehat - Yonathan Yonathan (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
The process of distributing goods is precisely determined from the transportation service provider used. The transportation used will affect a supply chain can be fulfilled properly or not. The decision to choose the right vendor is based on the selection of criteria from each service provider that suits the needs of the company itself. The selection of the wrong criteria will have an impact on the services provided to customers, one of which is the delay factor. Delays that occur are dominated by shipping by land. Analysis of the selection of the right vendor is done by applying the AHP and TOPSIS methods. The criteria used consist of price, quality, delivery, flexibility and reliability. Application of AHP and TOPSIS methods will provide an assessment of each of these vendors so they can determine the best vendor. The selection of the best vendor starts from determining the weight of each predetermined criterion. Each criterion will be correlated with each other which will then be weighted by each criterion. The results of determining the best vendor are obtained with the highest weight value of 0.807 obtained by Japung using the TOPSIS method.